Causes of Restrictiveness Policies on Foreign Direct Investment in OECD and Non-OECD Countries - Naushahi, Muhammad Mudassar; Kanwal, Asma; Batool, Irem; Hafeez ur Rehman (iRASD Journal of Economics, 2024)
Foreign direct investment (FDI) is considered a significant tool to transform modern technologies and innovation from developed to developing countries. Unfortunately, some countries impose FDI restrictions for economic, political, and social reasons. The present study assesses the role of different restrictive policies on FDI inflows in OECD and non-OECD countries. The empirical results are estimated by using panel quantile regression (PQR) at the median quantile from 1998 to 2022. It uses the all-restrictiveness policies index and its four subtypes: equity, key foreign personnel, screening and approval, and operational restrictions; the data is extracted from the OECD database. The study concluded that all restrictiveness policy indexes and their subtypes in OECD countries propose the inverted U-shaped curve. In contrast, in non-OECD countries, it shows the U-shaped relationship to determine the FDI inflows. Furthermore, this study also examines the individual countries using the marginal effect. In OECD countries, Australia, Canada, Mexico, and New Zealand have imposed higher restrictions, which reduces the FDI, while in non-OECD countries case, China, Indonesia, Malaysia, and the Philippines imposed higher restrictions, which increased FDI inflows. This study recommends that OECD countries reduce the FDI restrictiveness policies while non-OECD countries should increase it.